2008
DOI: 10.1111/j.1600-0897.2008.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ARTICLE: Cytokine Gene Polymorphisms in Recurrent Spontaneous Abortions: A Comprehensive Review

Abstract: Multiple cytokine polymorphisms were reported to be associated with RSA. However, a majority of studies were not confirmed by other investigators or refuted by others. Inconsistent study results might be related to: (i) the production of these cytokines is partly under genetic controls and other factors affect cytokine levels; (ii) ethnic background, environmental factors, and selection criteria for study populations are different and (iii) the possibilities exist that multiple cytokine gene polymorphisms or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 144 publications
(300 reference statements)
4
48
0
Order By: Relevance
“…6 Cytokine gene polymorphisms have been associated with certain inflammatory and infectious diseases, including some obstetric disorders. [7][8][9][10] The relationship between PE and single-nucleotide polymorphisms (SNPs) in cytokine genes has been investigated, but is still unclear. [11][12][13][14][15] The controversial results reported by different investigators may in part be because of selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…6 Cytokine gene polymorphisms have been associated with certain inflammatory and infectious diseases, including some obstetric disorders. [7][8][9][10] The relationship between PE and single-nucleotide polymorphisms (SNPs) in cytokine genes has been investigated, but is still unclear. [11][12][13][14][15] The controversial results reported by different investigators may in part be because of selection criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are conflicting regarding its association with RPL. Multiple studies have not yet shown any significant association between RPL and genetic polymorphisms of IL-1β, however ones have found significant associations between them (pooled odds ratio (OR) 2.12 (95 % confidence interval (CI) 1.04 to 4.33)) [77,115,116]. One study also noted a relationship between RPL and IL-1RA, IL1RN*2, and IL1RN*3 [115].…”
Section: Il-1mentioning
confidence: 96%
“…One meta-analysis performed did not show any significant association between RPL and genetic polymorphisms of IL-10, however other individual studies have noted a statistically significant associations (especially with IL-10 alleles -1082 and -592) [77,115,117,119,120]. Overall, the role of IL-10 in RPL still needs further exploration.…”
Section: Il-10mentioning
confidence: 97%
“…The main objective of the present study was to determine the effect of IL-10 -1082G/A gene promoter polymorphism in spontaneously aborted foetuses in addition to their parental groups. IL-10 serves a dual role in the production of pro-inflammatory cytokines and acts as an important anti-inflammatory cytokine at foeto-placental interface [21][22][23]. Pro-inflammatory cytokines (IL-1, IL-2, IL-12, IFN-γ, TNF-∝, IF-3) and anti-inflammatory cytokines (IL-4, IL-13, TGF-β) counter regulate each other such that they maintain a balance in their production resulting in normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%